The (non)-impact of democracy on levels of political risk. An evaluation of the relationship between levels of democracy and the political risk facing the oil and gas industry in Angola - Garcia, Anna Valentina Troeng (Stellenbosch : Stellenbosch University, 2015)
Thesis (MA)--Stellenbosch University, 2014.